Risk Procyclicality and Dynamic Hedge Fund Strategies: An Application of Kalman Filter to Time-Varying Alpha and Beta - Racicot, François-Éric; Théoret, Raymond (Université d'Ottawa | University of Ottawa, 2012)
Traditional financial institutions like banks follow procyclical risk strategies, i.e. they increase their leverage in economic expansions and reduce it in contractions, which leads to a procyclical behaviour for their betas and other risk and financial performance measures (Rajan, 2005, 2009; Shin, 2009; Jacque, 2010; Gennaioli et al., 2011). Consistent with the returns spectrum of many hedge fund strategies which displays a high volatility at business cycle frequencies, we study, in this paper, the cyclical aspects of hedge fund strategies, a subject quite neglected in the literature. To do so we rely on two procedures: conditional modelling and Kalman filtering of hedge funds alpha and beta. We find that hedge funds betas are usually procyclical. Our results also show that the alpha is often high at the beginning of a market upside cycle but as the demand pressure increases, it progressively shrinks, which suggests that the alpha puzzle documented in the financial literature is questionable when cast in a dynamic setting.